Cnidocyst structure and the biomechanics of discharge - Özbek, Suat; Balasubramanian, Gnana Prakash; Holstein, Thomas W. (Toxicon, 2009)
The cnidocyst is the defining organelle of the cnidarians, used for capture of prey and defense. It consists of a cylindrical capsule, which releases a long tubule upon triggering. Cnidocysts develop inside a giant post-Golgi vesicle by a sequential accumulation of proteins from the Golgi apparatus. Traditionally three types of cnidocysts are distinguished: nematocysts, spirocysts, and ptychocysts. Here we focus on nematocysts, the prototypic cnidocyst and by far most diverse group of cnidocysts in this phylum. The mature nematocyst capsule comprises a collagenous polymer with remarkable biophysical properties, able to withstand an osmotic pressure of 150bar. Release of the capsule and discharge is probably initiated by classical exocytosis. High-speed studies revealed the kinetics of discharge to be as short as 700ns, generating an acceleration of 5,400,000×g and a pressure of 7.7GPa at the site of impact of the spines onto the prey. Thus nematocysts comprise a powerful molecular spring mechanism releasing energy stored in the wall polymer in the nanosecond time range. During the last few years, genomic, biochemical and structural studies have helped to unravel the molecular composition of the nematocyst supra-structure. Here we summarize these findings and present an integrative view of mechanical and molecular aspects that have shaped the nematocyst during evolution.